In Search of an Alternative to the Liberal Democratic Party. The Case of Akai Ohi’s Electoral Campaign in 2021 Japanese General Election (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The Liberal Democratic Party (LDP) won the Lower House Elections, held on October 31, 2021. The Japanese Party obtained an undisputed victory after a year of harsh criticism addressed to the Suga Cabinet, run by the then LDP party chief, for his ineffective management of the Pandemic crisis. How can the long and almost unchallenged rule of the LDP over Japanese politics, from its foundation in 1955 to the last electoral success, be explained? This paper addresses the topic from an historical perspective, focusing on dr. Akai Ohi’s political campaign in the last General elections. Dr. Ohi (1980) is a Japanese political scientist who ran as a candidate for the Constitutional Democratic Party, the main opposition party, in the second constituency of Hiroshima Region, one of the LDP historical strongholds. The cornerstone of his political campaign was the establishment of the electoral alliance with the Communists in his constituency. The dialogue with dr. Ohi reported in this article explores his experience as a candidate and his analysis as a political scientist.
Keywords: Japan; Politics; Liberal Democratic Party; Election Campaigns; Center-left alliance